The Case Report : Challenges in the Management of Pneumothorax for COVID-19 Patient - Permatasari, Adinda Pramitra; Rakhma, Sastia; Putra, Ngakan Putu Parsama (Universitaas Brawijaya, 2023)
INTRODUCTION : Pneumothorax has been reported in minority of COVID-19 cases. Spontaneus Pneumothorax is an uncommon complication of COVID-19. The incidence and risk factors are still unknown. Here we will review where there are challenges with case of Pneumothorax in COVID-19 patients. CASE ILLUSTRATION : We report one case at Dr. Saiful Anwar hospital, a 42 years old man was diagnosed with Spontaneous Pneumothorax and tested positive for COVID-19 via nasopharyngeal swab. Management in this case requires consideration from emergency treatment, risk of virus transmission and the aerolization of the procedure. Invasive procedure such as insertion chest tube and pharmacologic therapy be the treatment in this case. After 2 weeks of treatment, there was improvement on clinical and radiological imaging. DISCUSSION : Various strategies to reduce the risk of exposure to COVID-19 infection on Spontaneus Pneumothorax. This literature discusses about the risk factor that lead to Pneumothorax with COVID-19 and the management of Pneumothorax cases in COVID-19 patients. CONCLUSION: Spontaneous Pneumothorax is a rare complication of COVID-19. Management in this case requires consideration from emergency treatment, risk of virus transmission and the aerolization of the procedure. Key words : Pneumothorax; COVID-19; Chest Tube